2017
DOI: 10.1007/s13197-017-2880-5
|View full text |Cite
|
Sign up to set email alerts
|

Study on the mobility of water and its correlation with the spoilage process of salmon (Salmo solar) stored at 0 and 4 °C by low-field nuclear magnetic resonance (LF NMR 1H)

Abstract: Low-field nuclear magnetic resonance (LF NMR) was used to investigate the water mobility of salmon during cold storage and the correlation between texture, freshness, sensory quality and transversal relaxation times (T) of salmon were studied. With the increasing of cold storage time, trapped water (T), sensory, water holding capacity and cooking loss were descended while free water (T), TVB-N and TBA were increased steadily, that reflected the quality of salmon quality visually. There was a significant correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 35 publications
7
47
0
Order By: Relevance
“…Sánchez‐Valencia et al reported that the shift of immobilized water towards the lower relaxation time in hake was more significant at higher storage temperature, and the relative abundance of immobilized water decreased with storage time . Significant decreases in relaxation time and population of immobilized water were also observed in salmon and yellowfin tuna during 0 and 4 °C storage . The progressive decrease in the immobilized water relaxation time could be explained by the shrinkage of muscle fiber of beef during storage, which has been reported in a previous publication .…”
Section: Resultssupporting
confidence: 52%
“…Sánchez‐Valencia et al reported that the shift of immobilized water towards the lower relaxation time in hake was more significant at higher storage temperature, and the relative abundance of immobilized water decreased with storage time . Significant decreases in relaxation time and population of immobilized water were also observed in salmon and yellowfin tuna during 0 and 4 °C storage . The progressive decrease in the immobilized water relaxation time could be explained by the shrinkage of muscle fiber of beef during storage, which has been reported in a previous publication .…”
Section: Resultssupporting
confidence: 52%
“…Water represented by T 22 was located outside myofibrils and first decreased and then increased with storage time. The variations were clear and in agreement with previous studies (Pearce, Rosenvold, Andersen, & Hopkins, ; Wang et al, ). Temperature fluctuations accelerated enzyme activity and the growth of microorganisms, which decreased the free water in the late period of storage (the sale and home storage stage).…”
Section: Resultssupporting
confidence: 92%
“…The signal with a T 2 of T 22 (free water) was easily lost during storage and transportation. The amount of free water decreased, causing the drip loss to increase (Wang et al, ). A high pH value has been proposed to cause water migration and is caused by organisms that degrade food (Gram et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TVB-N value in CK1 reached an unaccepted level (31.32 mg/100 g) on the 12th day and the samples with MAP incorporated with bioactive edible coating had lower TVB-N values compared with CK1 and CK2, especially 70% CO 2 /30% N 2 of MAP. The dominant reason was that the high concentration of CO 2 could retard bacterial action in the conversion of trimethylamine oxide (TMAO) into trimethylamine (TMA), which was one of the main substrates for the production of volatile bases [17].…”
Section: Quality Attributesmentioning
confidence: 99%